Ekonomi Syariah Sebagai ‘Trend’ di Era Globalisasi - Jefri Putri Nugraha (Falah: Jurnal Ekonomi Syariah, 2016)
Islam is a universal religion that regulates all dimensions of human life both; the world and the hereafter. Islam has also arranged economic problems since Islam was revealed through the Prophet Muhammad. Al-Quran and al-Hadith as the main reference of sharia economic thought. Islamic finance has become an economic system that was born along with the birth of Islam, but only this decade Islamic economic system become trending topic of discussion. Considering followers conventional notions began to look at the economic system of Syariah. In the era of globalization, there are a tendency in economic development for more attention to ethics in economic activity. This paper aims to explore in depth discussion on the trend of global economic and its development at the same time, reveals the opportunities and challenges in the economic development of sharia in the context of global economic development era.